Cord Meyer papers - Meyer, Cord, 1920-2001.
Correspondence; journal (1945-1965); newspaper columns, speeches, lectures, and other writings; and scrapbooks and photographs. Correspondence chiefly relates to Meyer's activities on behalf of one-world government and his association with the United World Federalists, to his family and personal life, and to his autobiography, entitled Facing Reality: From World Federalism to the CIA (1980). Includes correspondence pertaining to and copies of columns on foreign affairs written by Meyer for the Washington Times from 1990 to 1997. Correspondents include his mother, Katharine Thaw Meyer, his son, Mark Meyer, his brother, William B. Meyer, his mother-in-law, Ruth P. Pinchot, and his colleague at the Central Intelligence Agency, James Angleton.
Intelligence officer, internationalist, and newspaper columnist. Died 2001.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Angleton, James, -- 1917-1987 -- Correspondence; Meyer, Katharine Thaw -- Correspondence; Meyer, Mark, -- 1950- -- Correspondence; Meyer, William B., -- 1924- -- Correspondence; Pinchot, Ruth P. -- Correspondence; United States. -- Central Intelligence Agency; United World Federalists (U.S.); Washington times (Washington, D.C. : 1982); Internationalism; Journalism -- United States; Internationalists; Intelligence officers; Journalists